An Exploratory Study of Graduate Student Unions in Canada - Zinni, Deborah; Singh, Parbudyal; MacLennan, Anne (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2005)
Graduate student unions are beginning to attract attention in Canada and the United States. In Canada, unionization on campuses is especially important for organized labour, as union density has dropped below 30 percent for the first time in five decades. Graduate student unionization is also important in the wider context of precarious employment in North America. Despite the decline in overall union density, graduate student unions have continued to grow in the past decade. However, there is a paucity of scholarly research in this area. In this article, we trace the historical origins of graduate student unions in Canada, discuss relevant legal concerns, analyze pertinent collective bargaining and strike issues, and suggest avenues for future research.